2018
DOI: 10.3390/molecules23123245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rich-Polyphenols Extract of Dendrobium loddigesii on Anti-Diabetic, Anti-Inflammatory, Anti-Oxidant, and Gut Microbiota Modulation in db/db Mice

Abstract: Dendrobium is a traditional Chinese herb with anti-diabetic effects and has diverse bibenzyls as well as phenanthrenes. Little is known about Dendrobium polyphenols anti-diabetic activities, so, a rich-polyphenols extract of D. loddigesii (DJP) was used for treatment of diabetic db/db mice; the serum biochemical index and tissue appearance were evaluated. In order to gain an insight into the anti-diabetic mechanism, the oxidative stress index, tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and gut micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 54 publications
3
56
0
1
Order By: Relevance
“…Although there was not significant difference in Bacteroidetes and Firmicutes between the NC and model groups, the Bacteroidetes to Firmicutes ratio was decreased in model group. The reduction in Bacteroidetes and the increase in Firmicutes may be related to the increased ability to harvest energy from food and cause low-grade systemic inflammation, eventually damaging the organism [45,46]. Additionally, we found that the ratio of Bacteroidetes to Firmicutes was increased in SCML groups, suggesting that intestinal flora imbalance was improved after SCML treatment.…”
Section: Discussionmentioning
confidence: 66%
“…Although there was not significant difference in Bacteroidetes and Firmicutes between the NC and model groups, the Bacteroidetes to Firmicutes ratio was decreased in model group. The reduction in Bacteroidetes and the increase in Firmicutes may be related to the increased ability to harvest energy from food and cause low-grade systemic inflammation, eventually damaging the organism [45,46]. Additionally, we found that the ratio of Bacteroidetes to Firmicutes was increased in SCML groups, suggesting that intestinal flora imbalance was improved after SCML treatment.…”
Section: Discussionmentioning
confidence: 66%
“…Dendrobium is a HM clinically used for the treatment of T2DM and its complications, and dendrobium polyphenols are its main constituents that exert diverse pharmacological effects (Paudel et al, 2018 ). A study on the effects of a polyphenol-rich extract of Dendrobium loddigesii (DJP) in diabetic mice identified anti-inflammatory activities of DJP for T2DM treatment through a reduction of IL-6 and TNF-α expression, which was correlated with the modulation of gut microbiota, including an increase of the Bacteroidetes to Firmicutes ratio and Prevotella/Akkermansia abundance and a decrease in the abundance of S24-7 / Rikenella / Escherichia coli (Li et al, 2018 ) ( Table 1 ).…”
Section: Host-gut Microbiota-herbal Medicine Interaction During T2dm mentioning
confidence: 99%
“…72 Increased Bacteroidetes to Firmicutes has also shown after intervention with Qijian mixture (Astragalus membranaceus, Ramulus euonymi, Coptis chinensis, and Pueraria lobata) and extract of D. loddigesii. 73,74 Increased abundance of Akkermansia was also associated with glucose-lowering properties of polyphenolrich extracts of cranberry. 75 Water-ethanol extract of green macroalgae Enteromorpha prolifera and Oil tea (green tea and ginger) enriched Lachnospiraceae has been reported after intake of in animal studies, 76,77 wherein it was suggested to underlie its beneficial impact on glycemic control.…”
Section: Herbal Agents Used To Treat T2d and Gut Microbiotamentioning
confidence: 99%